Toll-like receptors, IFN-γ and IL-12 expression in bovine leukemia virus-infected animals with low or high proviral load - Nieto Farías, María Victoria (2016)
Bovine leukemia virus (BLV) infection is widespread mainly in dairy cattle and 5-10% of infected animals will die due to lymphosarcoma; most cattle remain asymptomatic but 30% develop persistent lymphocytosis (PL). BLV transmission depends on infected cell exchange and thus, proviral load is determinant. Understanding the mechanisms which govern the control of viral dissemination will be desirable for the design of effective therapeutic or preventive strategies for BLV. The development of high proviral load (HPL) or low proviral load (LPL) might be associated to genetic factors and humoral immune responses, however cellular responses are not fully described. We aimed to characterize cytokines and toll-like receptors (TLR) expression related to the proviral load profiles. IFN-γ and IL-12 mRNA expression level was significantly higher in PBMC from infected cattle (LPL n = 6 and HPL n = 7) compared to uninfected animals (n = 5). While no significant differences were observed in IL-12 expression between LPL and HPL group, IFN-γ expression was significantly higher in LPL animals. Infected cattle exhibited higher expression levels of TLR3, 7-9. Animals with HPL had significantly higher expression of TLR7/8 than uninfected cattle. TLR8 and TLR9 were up-regulated in HPL group, and TLR3 was up-regulated in LPL group. This is the first report related to TLR gene expression in BLV infected cattle and represents evidence of the involvement of these receptors in BLV recognition. Further studies on different subpopulations of immune cells may help clarify their role in response to BLV and its consequences on viral dissemination.